Effect of vitamin D supplementation on cardiovascular risk in type 2 diabetes. Issue 5 (October 2019) - Angellotti, Edith; D'Alessio, David; Dawson-Hughes, Bess; Chu, Yan; Nelson, Jason; Hu, Peter; Cohen, Robert M.; Pittas, Anastassios G.
Summary: Background & aims: Whether vitamin D affects lipid profile and cardiovascular disease (CVD) risk is controversial. We evaluated the effect of oral daily vitamin D supplementation on lipid profile and CVD risk in patients with well-controlled type 2 diabetes. Methods: Secondary analysis in the vitamin D for established type 2 diabetes (DDM2) study, a double-blind, randomized, placebo-controlled clinical trial. 127 patients (mean age 60 years) with stable (HbA1c ≤ 7.5%) diabetes managed with lifestyle only or lifestyle plus metformin were randomized to receive 4000 IU/day of vitamin D3 (n = 66) or placebo (n = 61) for 48 weeks. Changes in lipid profile (total cholesterol, LDL-cholesterol, HDL-cholesterol, triglycerides [TG] and TG/HDL ratio), C-reactive protein and CVD risk (calculated according the American College of Cardiology/American Heart Association [ACC/AHA] guidelines) were assessed at week 24 and 48. Results: The mean [±SEM] plasma 25-hydroxyvitamin D [25(OH)D] level was higher in the vitamin D vs. the placebo group (20.5 ± 1.18 vs. −1.6 ± 1.2 ng/mL respectively; p < 0.001). There was no statistically significant change in lipid profile, C-reactive protein or CVD risk. Among patients who were not on cholesterol medication (n = 32), vitamin D supplementation reduced TG compared to placebo at week 48 (−18.74 ± 8.91 vs. 9.69 ± 8.60 mg/dL respectively; p = 0.032). Conclusion: One year supplementation with vitamin D3 at 4000 IU/day did not affect lipid profile, C-reactive protein and CVD risk in patients with stable type 2 diabetes not selected for vitamin D deficiency, with the exception of improvement of TG among patients not on cholesterol medication. Registration: ClinicalTrials.gov Identifier NCT01736865 .